A Comparative Model for Selection of Opaque Wall Constructions in Hot and Humid Climates - Boostani, Haleh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
With the advent of the Industrial Revolution and its worldwide occurrence, the increased use of fossil fuels in the building sector have raised which caused energy crisis and global warming as a result of carbon dioxide emissions. The stated issues have led the authorities to develop a creative approach to confronting the crisis through energy efficiency policies. However, optimizing energy consumption should not result in losing thermal comfort in buildings. Therefore, these two approaches must be considered in the same direction and from the early stage of the building design. One of the main causes of excessive use of energy in buildings of severe climates (i.e., for heating and cooling purposes) is heat conduction through building external walls. Therefore selecting the optimal walls, with the approaches of energy efficiency and thermal comfort can be a great step in this direction particularly in regions with the severe climatic condition. However, the process of walls selection itself is another issue that requires comprehensive research on the subject, influential factors, evaluation criterion as well as the decision-making process. Accordingly, the present study, oriented to develop a comparative model selecting optimal opaque wall constructions in hot and humid climates based on four main evaluation criterion namely energy saving (by means of dynamic thermal simulation), thermal comfort (by means of Fanger’s PMV model), moisture control (by means of steady-state Glaser analysis) as well as the cost efficiency (by means of amortization time calculation). The reason why “hot and humid climate” was chosen was that the thermal behavior of the walls in such climates faces unpredictable factors due to the climate characteristics, such as moisture condensation and heat behavior in different periods of the year. Both research methods of qualitative and quantitative were employed in this study including literature survey, field survey, computer-based simulation, temperature monitoring, thermal and cost analysis as well as a simple multi-attribute rating technique (SMART) for the final assessment and the decision making process. To indicate the application of the developed multi-factor optimization model, a case study methodology was employed by means of a two-bedroom flat in Kish Island, Iran which is characterized by a “hot and humid climate”. The number of 10 wall cases were selected in accordance with the most commonly used wall constructions in the context (walls 1-5 and 10) besides suitable ones suggested by the literature review after a process of localization (in accordance with the context building code; walls 6-9). Based on the results wall 6 obtained the highest performance for energy saving and thermal comfort hours followed by walls 7, 8, 10 and 9 respectively. On the contrary, wall 3 obtained the worst result for energy saving and thermal comfort hours, followed by walls 1, 2, 5 and 4. In addition to energy saving and thermal comfort, based on Glaser analysis, condensation was occurred for walls 6 and 7, which employed insulation internally and externally respectively. However, since the results for the condensation rate is below the limit, the walls are not at the risk for condensation at all. Further, the results for cost efficiency indicated that the entire wall cases amortized their initial cost less than the limit of 10 years while wall 3 considered to be the wall with the longest amortization time period of 9.1 years. On the contrary, wall 10 considered being the wall with the shortest amortization time period of 4.8 years. As a result for the final assessment and overall grading of the SMART in terms of energy saving, thermal comfort and cost efficiency for the entire simulated wall constructions, wall 6 obtained the highest overall grade; this is the opposite for wall 3, obtaining the lowest grade among the entire simulated cases. Paying attention to the results, it can be deducted that the walls that suggested by the literature review and as a result of localization process (employing thermal insulation) showed more energy saving and thermal comfort potential at all. It also should be highlighted that since the developed model is inherently comparative in which multiple evaluation factors are considered, the result is obtained generally, on aggregate. Based on the findings and in accordance with the walls total grades through the SMART, the most efficient walls were the ones formed during the localization process (i.e., walls 6-9) in addition to a 40-cm adobe wall (i.e., wall 10) as the representative case for traditional walls used in ancient architecture of Kish Island. As a consequence, the results of the case study revealed that the application of the developed model has the potential to save cost and energy, improve the thermal quality of the indoor environment as well as predicting the risk of condensation in buildings’ walls of hot and humid climates. Keywords: Multi-Factor Optimization Model, Energy saving, Thermal Comfort, Moisture Control, Cost Efficiency, Localization

ÖZ: Endüstri Devrimi'nin gelişi ve dünya çapında yaygınlaşması ile birlikte, karbon dioksit emisyonlarının bir sonucu olarak enerji krizine ve küresel ısınmaya neden olan inşaat sektöründe fosil yakıtların kullanımının azaltılması gündeme gelmiştir. Dolayısıyla, bunun sonucunda enerji koruma politikaları geliştirmesine yol açılmıştır. Bununla birlikte, enerji tüketimini optimize etmek binalarda ısıl konforun gözardı edilmesi anlamını taşımaz. Bu nedenle, bu iki yaklaşım, bina enerji kullanımı stratejilerinin tasarımında eşit ve aynı yönde düşünülmelidir. Binalarda enerji tüketiminin ana nedenlerinden biri, dış duvarlar (yani opak kısım) yoluyla ısı transferidir. İster içten dışa, ister tersi olsun, bu değişim, bina sakinleri için ısıl rahatsızlığa neden olur ve ısıtma ve soğutma mekanik cihazlarının kullanılması ihtiyacını ortaya çıkarır. Bu nedenle, uygun duvarların seçimi, enerji verimliliği ve ısıl konfor yaklaşımı parametreleri dikkate alınarak yapılmalıdır. Ancak, uygun duvar uygulamasının nasıl belirleneceği, kapsamlı bir seçim ve karar verme yöntemi gerektiren bir diğer konudur. Buna göre, bu çalışma, sıcak iklimlerde opak duvar konstrüksiyonlarını karşılaştırmalı olarak seçmek için bir yöntem geliştirmeye yöneliktir. Sıcak iklimin seçilmesinin sebebi, iklim özelliklerinden dolayı bu iklimlerde duvarların ısıl davranışlarının tahmin edilemeyen faktörlerle karşı karşıya kalması, kapsamlı bir araştırma için daha uygun olan birkaç yaklaşımı tanımlamaktır. Çok faktörlü optimizasyon yönteminin geliştirilmesi, literatür taramasının öne sürdüğü uygun duvarların yanı sıra, yerel kullanım alanı bulmuş yaygın uvar türleri arasında yapılacak seçimin, enerji verimliliği, ısıl konfor ve ekonomik analizleri de içeren çok faktörlü optimizasyon yöntemini geliştirilerek değerlendirilmesi hedeflenmiştir. Önerilen model yapılan saha çalışması ile test edilmiştir. Saha çalışmasında literatür taraması ile önerilen iç duvarlar, yerel kullanım alanı bulmuş duvar seçenekleri ile mukayese edilerek sonuca ulaşılmıştır. Açıkçası, önerilen yöntemin, sıcak ve nemli bir iklimde opak duvarları seçmek için kapsamlı bir yöntem olduğu söylenemez, ancak bu yöntemin, olası seçenekleri kullanarak, daha iyi bir seçim tekniğine yol açabileceği söylenebilir. Anahtar Kelimeler: Enerji verimliliği, İsıl Konfor, Optimizasyon Yöntemi, Duvar Yapımı, Sıcak ve Nemli İklim
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2019. Supervisor: Assist. Prof. Dr. Polat Hançer.
Keywords: Architecture; Architecture--Buildings--Climatic Factors; Multi-Factor Optimization Model; Energy saving; Thermal Comfort; Moisture Control; Cost Efficiency; Localization